Scooby-Doo! and the ghastly giant - McCann, Jesse Leon.; Duendes Del Sur (Firm); Cartoon Network (Television network) (New York : Scholastic, 2003)
While working as counselors at Craggy Mountain summer camp, Scooby-Doo and the gang are unsettled when one of their ghost stories starts coming true.
"Cartoon Network."
"RL1"--Cover p. [4].
"004-008"--Cover p. [4].
3.4
K-3
K-3
Keywords: Scooby-Doo (Fictitious character) -- Fiction; Dogs -- Fiction; Camps -- Fiction; Giants -- Fiction; Mystery and detective stories; Scooby-Doo (Fictional character) -- Fiction; Dogs -- Fiction; Camps -- Fiction; Giants -- Fiction; Mystery fiction; Mystery fiction